Soviet Cultural Canon in 1930 – 1950 - Dokuchaev, Ilya I. (Global Journal of Cultural Studies, 2023)
The article contains the rationale for the methodological principles of studying the history of values in culture. The most important theoretical provisions are given, which allow to determine the essence, structure and historical sources of the study of values in culture. The structure of culture is analyzed in detail in its superficial and deep versions, that is, as a producing value model (canon) and a derivative system of artifacts. The historical types of values in culture are described, that is, their historical typology is proposed. The value model of Soviet culture is studied in detail in all its key components, such as social institutions, communication, technology and technology, pedagogy and medicine, economics, material culture, language, art, and the type of person.